2019
DOI: 10.1182/blood-2019-127754
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Virus Therapy with HSV-1 for Hematologic Malignancies

Abstract: Background: Oncolytic virus (OV) is an attractive and rapidly developing antitumor therapy. OVs preferentially replicate in tumor cells and exhibit a tumoricidal activity without damaging normal cells. G47Δ is a herpes simplex virus (HSV)-1 genetically engineered to enhance tumor selectivity and immunogenicity. Clinical trials of G47Δ have been conducted for brain and prostate cancers. Anecdotal reports that leukemia and lymphoma shrink following viral infection imply effectiveness of OV therapy against hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We recently found that oncolytic HSV‐1 kills various lineages of haematological tumour cells and that the expression of nectin‐1, a receptor for glycoprotein D of HSV‐1, 25 is a decisive factor for the cytotoxic effect (submitted) 26 . Together with this finding, the present study suggests that oncolytic HSV‐1 is a viable therapy for nectin‐1‐expressing plasma cell neoplasms and that the combination with lenalidomide may represent a rational therapeutic option that exploits direct cytotoxic as well as indirect immune‐mediated mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that oncolytic HSV‐1 kills various lineages of haematological tumour cells and that the expression of nectin‐1, a receptor for glycoprotein D of HSV‐1, 25 is a decisive factor for the cytotoxic effect (submitted) 26 . Together with this finding, the present study suggests that oncolytic HSV‐1 is a viable therapy for nectin‐1‐expressing plasma cell neoplasms and that the combination with lenalidomide may represent a rational therapeutic option that exploits direct cytotoxic as well as indirect immune‐mediated mechanisms.…”
Section: Discussionmentioning
confidence: 99%